2020
DOI: 10.1590/1516-4446-2020-1050
|View full text |Cite
|
Sign up to set email alerts
|

The course and clinical correlates of panic disorder during the postpartum period: a naturalistic observational study

Abstract: Objective: To investigate the course of panic disorder and its demographic and clinical correlates during the postpartum period. Methods: Data were collected from 38 consecutive postpartum women diagnosed with panic disorder. Psychiatric assessments were carried out on the first day after delivery and at 6-8 weeks postpartum. During the first assessment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(37 reference statements)
0
2
1
Order By: Relevance
“…In another study that was conducted in Germany, the researchers recruited 128 women with PD and demonstrated that PD symptoms during pregnancy are fewer, while the postnatal period seems to increase the risk for the onset or worsening of PD symptoms [ 16 ]. These results were inconsistent with another study findings, that pregnant women with a short period of panic disorder may experience significant relief in the severity of panic disorder symptoms during the postnatal duration [ 17 ].…”
Section: Discussioncontrasting
confidence: 97%
“…In another study that was conducted in Germany, the researchers recruited 128 women with PD and demonstrated that PD symptoms during pregnancy are fewer, while the postnatal period seems to increase the risk for the onset or worsening of PD symptoms [ 16 ]. These results were inconsistent with another study findings, that pregnant women with a short period of panic disorder may experience significant relief in the severity of panic disorder symptoms during the postnatal duration [ 17 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Faisal-Cury et al 1 explore a much important but often neglected theme -the decline of sexual life in the postpartum period, particularly among women with postpartum depression. The same is true for the study of Aydogan et al, 2 who studied a group of pregnant women with panic disorder, showing alleviation of symptoms during the postpartum period. Finally, the study of Uguz & Ak 3 presents data on the effectiveness of cognitive-behavioral therapy in women with generalized anxiety disorder during pregnancy.…”
mentioning
confidence: 53%
“…The current study investigated psychophysiological variables as potential mediators of treatment response, an extension of previously published studies (Nelson et al, 2020). Results indicate that patients with a short disease span may experience substantial relief in the severity of panic symptoms during the postpartum period (Aydogan et al, 2020).…”
Section: Panic Disorder Symptomsmentioning
confidence: 95%